2020
DOI: 10.1007/s41603-020-00111-5
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant Evangelicalism in the COVID-19 Crisis: Reactions and Responses from Brazilian Evangelical Churches in Florida

Abstract: This article seeks to analyze the reactions and responses of three churches of the Brazilian diaspora in Florida, United States, to the COVID-19 pandemic. Drawing on sermons posted on YouTube and Facebook in March, April, and May, we argue that Brazilian immigrant churches in Florida reacted to the pandemic in civil, theological, practical ways. We begin by providing a general introduction to evangelicalism in the United States and its influence in Brazilian evangelical life to give a historically sound backgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…p. 42). Likewise, other studies have indicated that Macedo continued demonology in relation to the COVID-19 virus (Serrão and Chaves 2020 , p. 246), insisting on keeping churches open as it would be worse for people to lose the protection of God than to be infected with the demonic virus (von Sinner and Zeferino 2022 ). Whether and to what extent Macedo wields interpretive authority over viruses and diseases in local churches abroad is what this article aims to explore.…”
Section: Doctrines Controversies and Epistemes About Viruses And Heal...mentioning
confidence: 98%
See 1 more Smart Citation
“…p. 42). Likewise, other studies have indicated that Macedo continued demonology in relation to the COVID-19 virus (Serrão and Chaves 2020 , p. 246), insisting on keeping churches open as it would be worse for people to lose the protection of God than to be infected with the demonic virus (von Sinner and Zeferino 2022 ). Whether and to what extent Macedo wields interpretive authority over viruses and diseases in local churches abroad is what this article aims to explore.…”
Section: Doctrines Controversies and Epistemes About Viruses And Heal...mentioning
confidence: 98%
“…2021 , p. 51). In this context, the Brazilian Universal Church of the Kingdom of God (UCKG) has been frequently addressed as a protagonist in the critique of measures to contain the COVID-19 virus in Brazil (Capponi 2020 ; Serrão and Chaves 2020 ; Yendell et al. 2021 ; Martins and Miletta 2021 ; von Sinner and Zeferino 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…9, marzo-agosto 2022, pp. 174-196 Cristianismo postdenominacional y coronavirus:... suplir la falta de reuniones cara a cara (Campbell, 2020;Serrão y Chaves, 2020).…”
Section: #Masvidaencasaunclassified
“…Es así como, a partir de los fenómenos sociales contemporáneos en interacción con la religión, junto al contexto de anormalidad que ha implicado el confinamiento por el Covid-19 (Baker et al 2020;Calvo, 2021;Giménez Béliveau, 2021;Bandeira and Carranza, 2020;Serrão and Chaves, 2020), el estudio de la religión contemporánea se enfrenta a nuevos desafíos. De esta manera, las teorías clásicas en antropología y sociología de la religión necesitan ser evaluadas en un contexto contemporáneo que difiere del momento en que fueron formuladas.…”
Section: Introductionunclassified